2020
DOI: 10.1097/jcn.0000000000000739
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Examination of the Dutch Objective Burden Inventory in Heart Failure Caregivers

Abstract: Background Psychometric properties of the 38-item version of the Dutch Objective Burden Inventory (DOBI) have been evaluated primarily in older female caregivers, with no published studies that vary by a different gender and age distribution. Objective The aim of this study was to test the construct validity and reliability of the DOBI in caregivers of individuals with heart failure from the United States and other countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Most lived with someone else (82.83%). A detailed review of participant characteristics can be found in the previous psychometric analysis of the objective component of the DOBI 12 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most lived with someone else (82.83%). A detailed review of participant characteristics can be found in the previous psychometric analysis of the objective component of the DOBI 12 …”
Section: Resultsmentioning
confidence: 99%
“…Psychometric analyses of the objective component support its construct validity and reliability, using caregivers of individuals with HF. However, although the DOBI has been used in many studies to examine caregiving burden, published data are unavailable regarding the psychometric properties of the subjective component of the DOBI 10–13 . Furthermore, this analysis is unique in that participants in previous studies were mostly older women, whereas the current study had a diverse group of younger caregivers and an almost equal percentage of male and female participants.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…[9][10][11][12][13] Caregiver burden is also common in HF caregivers and encompasses both task frequency and the perceived associated burden. [14][15][16][17] Additionally, providing HF care in the home is accompanied by numerous life changes, including decreased time for family and social activities and difficulty coping with stress. 5,7,14,18 Further, research suggests a negative feedback loop, with more negative perceptions of life changes associated with higher levels of depression.…”
Section: Introductionmentioning
confidence: 99%